Serum calprotectin as a predictive biomarker in the treatment of psoriasis vulgaris with methotrexate - Ashraf M Hamza; Eman M Hassan; Hanaa M Donia; Yasmin M Maamon (Wolters Kluwer Medknow Publications, 2019)
Background Psoriasis is a chronic inflammatory disease that poses a challenge in its pathogenesis and treatment. Calprotectin is upregulated in psoriatic epidermis and is supposed to have a role in the inflammatory process of psoriasis. Calprotectin was suggested as a biomarker to detect responders to methotrexate in juvenile idiopathic arthritis. Objective To evaluate the relation of calprotectin serum level and psoriasis severity and to assess if it can predict response to methotrexate and disease relapse after stoppage of the treatment. Patients and methods Thirty patients with psoriasis vulgaris and 30 controls were included. Serum calprotectin was measured in controls and in patients before and after methotrexate therapy for 3 months. The patients were followed up for 6 months to detect disease stability or relapse and its relation to calprotectin level at the end of therapy. Results Higher calprotectin level in psoriatic patients was detected before methotrexate treatment than after treatment. Significant positive correlation was found between serum calprotectin and psoriasis area and severity index score. Calprotectin was higher in patients before starting methotrexate in those defined as responders than nonresponders (P=0.015) and can predict response to treatment with a cutoff value of 60 ng/ml (sensitivity 82.35% and specificity 69.23%). The level of calprotectin was higher in patients during their clinical remission who relapsed after stoppage of methotrexate than the nonrelapsed cases (P=0.021) and can predict the relapse with a cutoff value of 56.5 ng/ml (sensitivity 66.67% and specificity 100%). Conclusion Calprotectin can be a marker of psoriasis severity. Higher level of baseline serum calprotectin can predict psoriatic patients who will improve on methotrexate therapy. In addition, higher calprotectin levels were associated with relapse risk after stoppage of methotrexate.